Mathematical modeling of seed dissemination with a colter drill across the planting acreage. Issue 1 (September 2020) - Evchenko, A V; Shevchenko, A P; Begunov, M A; Koval, V S; Algazin, D N
Abstract: The article is devoted to the development of a mathematical model of seed dissemination process with a colter drill equipped with a discharge channel across the feeding area. This mathematical model makes it possible to determine the optimal technological and constructive parameters of the colter drill of the planter.